Managing security services in heterogenous networks : confidentiality, integrity, availability, authentication, and access control /: confidentiality, integrity, availability, authentication, and access control. (2021) - Jeyanthi, N, 1977-; (Computer scientist), Ma, Kun; Perumal, Thinagaran; Thandeeswaran, N
No abstract available